Kingdom of the Netherlands : Netherlands; Selected Issues-The Labor Income Tax Credit in an International Perspective. (IMF Staff Country Reports; Country Report ;, 2001)
Compared with its U.S. and U.K. counterparts, the Labor Tax Credit (LTC) is likely to have more limited effects on incentives for primary-earners to enter the labor force, because of the smaller size of the credit. Any significant increase in the LTC to strengthen its effect on the still large poverty trap in the Netherlands is likely to be extremely expensive. Given the easy availability of part-time employment and the high marginal tax rates, the reduction in hours worked could be substantial in the Netherlands.